Inflammation as a driver of hematological malignancies - Saluja, Sumedha; Bansal, Ishu; Bhardwaj, Ruchi; Beg, Mohammad Sabique; Palanichamy, Jayanth Kumar (Frontiers in Oncology, 2024)
Hematopoiesis is a tightly regulated process that produces all adult blood cells and immune cells from multipotent hematopoietic stem cells (HSCs). HSCs usually remain quiescent, and in the presence of external stimuli like infection or inflammation, they undergo division and differentiation as a compensatory mechanism. Normal hematopoiesis is impacted by systemic inflammation, which causes HSCs to transition from quiescence to emergency myelopoiesis. At the molecular level, inflammatory cytokine signalling molecules such as tumor necrosis factor (TNF), interferons, interleukins, and toll-like receptors can all cause HSCs to multiply directly. These cytokines actively encourage HSC activation, proliferation, and differentiation during inflammation, which results in the generation and activation of immune cells required to combat acute injury. The bone marrow niche provides numerous soluble and stromal cell signals, which are essential for maintaining normal homeostasis and output of the bone marrow cells. Inflammatory signals also impact this bone marrow microenvironment called the HSC niche to regulate the inflammatory-induced hematopoiesis. Continuous pro-inflammatory cytokine and chemokine activation can have detrimental effects on the hematopoietic system, which can lead to cancer development, HSC depletion, and bone marrow failure. Reactive oxygen species (ROS), which damage DNA and ultimately lead to the transformation of HSCs into cancerous cells, are produced due to chronic inflammation. The biological elements of the HSC niche produce pro-inflammatory cytokines that cause clonal growth and the development of leukemic stem cells (LSCs) in hematological malignancies. The processes underlying how inflammation affects hematological malignancies are still not fully understood. In this review, we emphasize the effects of inflammation on normal hematopoiesis, the part it plays in the development and progression of hematological malignancies, and potential therapeutic applications for targeting these pathways for therapy in hematological malignancies.